2019
DOI: 10.1002/bdr2.1641
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic findings in arthrogryposis and congenital Zika syndrome: A case series

Abstract: Background Congenital arthrogryposis (CA) consists of congenital joint contractures that affect at least two joints in different parts of the body. Approximately, 80% of CA cases are neurogenic, with changes to the formation, structure or functioning of the central and/or peripheral nervous systems. Most abnormalities are triggered either by motoneurons decreased activation in the corticospinal tract or by direct motoneurons injury. There had been few reports in the literature correlating congenital infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…1 Arthrogryposis, one of the most limiting extracranial conditions, involves multiple joint contractures, and its association with CZS has been described with flexed wrists as the most common finding. 18 Other manifestations include talipes equinovarus (clubfoot), valgus deviation, and bilateral rotation of the lower limbs, and hip dislocation. 18 Physical therapy is recommended to improve postural control and mobility, 19 and has been suggested to improve this patient's clubfoot and angulation of the extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Arthrogryposis, one of the most limiting extracranial conditions, involves multiple joint contractures, and its association with CZS has been described with flexed wrists as the most common finding. 18 Other manifestations include talipes equinovarus (clubfoot), valgus deviation, and bilateral rotation of the lower limbs, and hip dislocation. 18 Physical therapy is recommended to improve postural control and mobility, 19 and has been suggested to improve this patient's clubfoot and angulation of the extremities.…”
Section: Discussionmentioning
confidence: 99%
“…18 Other manifestations include talipes equinovarus (clubfoot), valgus deviation, and bilateral rotation of the lower limbs, and hip dislocation. 18 Physical therapy is recommended to improve postural control and mobility, 19 and has been suggested to improve this patient's clubfoot and angulation of the extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the authors did not describe the results of orthopedic treatment for these patients. Serpa et al 26 described the arthrogrypotic alterations in 17 infants diagnosed with CZS. It was noted that the upper limbs' proximal segments were less affected, with a compromised concentration in the distal region of the upper limbs.…”
Section: Zika Virusmentioning
confidence: 99%
“…The occurrence of painful hip dislocation is directly related to the severity of neurological involvement and the child's ambulatory status [2]. Many studies reported that children with CZS presented a higher incidence of hip dislocation and hip dysplasia [3][4][5]. Authors have noted that hips may begin to displace as early as 18 months of age; therefore, it is advisable that the hips should be examined radiologically malformations of cortical development and calcification of the cortical-subcortical junction.…”
Section: Introductionmentioning
confidence: 99%